Mediation Of Consumer Satisfaction Between Product Quality and Interest In Repurchase Wardah Powder At Matahari Department Store Jayapura - Muhammad Ridwan Rumasukun; Mohammad Aldrin Akbar Akbar; Yendra Yendra; Ulfi Lestiana Lafiatun (Economos : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of product quality on the purchase intention of wardah powder product at Matahari Departement Store Jayapura. The sampling method used purposive sampling with predetermined criteria. The sample of this research is 130 people. The results showed that product quality had no effect on repurchase intention, but had a positive effect on customer satisfaction. Customer satisfaction has a positive and significant effect on repurchase interest. Product quality has an effect on repurchase intention trought customer satisfaction as a mediating variable.